HOSPITAL SHIP: HEALTH SERVICES IN TAMBELAN ISLANDS - Soeselo, Daniel Ardian; Yolanda, Rennie; Pranata Tampubolon, Dedi (Mitramas: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
This article aims to share the experience of healthcare services we provided in the Tambelan Islands and build awareness that healthcare services in rural areas, especially the islands, are still minimal and receive little attention. Tambelan Islands are one of the rural areas in Bintan Regency, Riau Archipelago Province, Indonesia. Healthcare facilities in the Tambelan Islands are still minimal and inadequate, including surgical services. Patients with medical conditions accompanied by complications or requiring surgery must be referred to the West Kalimantan Hospital for approximately 15 hours by sea. DoctorSHARE Foundation and volunteer team provide healthcare services with the Floating Hospital facility to reach the rural area. Healthcare services include surgical specialists, antenatal care, and general practitioner services. We served 485 patients in the local community, including 43 patients requiring surgeries.